ETHICAL LEADERSHIP OF SCHOOL ADMINISTRATORS AFFECTING THE ORGANIZATIONAL COMMITMENT OF TEACHERS UNDER NAKHONNAYOK PRIMARY EDUCATIONAL SERVICE AREA - Pontep, Pitak; Chansilp, Manaphan; Sorapan, Chulalak (Journal of Educational Review Faculty of Education in MCU, 2026)
The objectives of this research were to: 1) investigate the level of ethical leadership of school administrators 2) assess the level of organizational commitment among teachers 3) examine the relationship between school administrators' ethical leadership and teachers' organizational commitment and 4) develop a predictive equation for school administrators' ethical leadership affecting teachers’ organizational commitment within the Nakhon Nayok Primary Educational Service Area Office. This study employed a survey research design. The sample consisted of 285 civil service teachers, obtained through stratified random sampling based on school size. The research instruments were questionnaires regarding ethical leadership and organizational commitment, with reliability coefficients of 0.99 and 0.97, respectively. Data were analyzed using descriptive statistics and simple regression analysis. The research findings revealed that 1) the overall level of ethical leadership of school administrators was at a high level 2) the overall level of organizational commitment of teachers was at a high level 3) there was a significant positive relationship at a high level between the ethical leadership of school administrators and teachers’ organizational commitment at the .05 level (r = .77) and 4) school administrators’ ethical leadership significantly predicted teachers’ organizational commitment at the .05 level, with a predictive power of 59.0%. The predictive equations in raw score and standardized score forms were ŷ = 1.620 + .641(x) and Ẑy = .769(Zx), respectively.